A case of cutaneous rosai-dorfman disease treated by intralesional injections of glucocorticoid - Yan-xia Yuan; Chun-xing Xu; Ru-zhi Zhang (Wolters Kluwer Medknow Publications, 2021)
A 45-year-old male presented with painless reddish-brown plaques and nodules that had infiltrated his shoulder and back for 3 months. From the clinical manifestations and histopathological findings, the patient was diagnosed with cutaneous Rosai-Dorfman disease. Intralesional injections of betamethasone (trade name: diprospan) were recommended and the lesions improved significantly after three treatments.